A baseline for assessing the ecological integrity of Western Amazon rivers - Elizabeth P. Anderson; Andrea C. Encalada; Thiago B. A. Couto; Claire F. Beveridge; Guido A. Herrera-R; Sebastian A. Heilpern; Rafael M. Almeida; Carlos Cañas-Alva; Sandra B. Correa; Lesley S. de Souza; Fabrice Duponchelle; Carmen Garcia-Davila; et al. (Communications Earth & Environment)
Abstract Amazon freshwater systems influence global hydroclimatic patterns, host unparalleled biological diversity, and support unique social-ecological systems. Rivers of the Western Amazon underpin this global importance with an outsized, underrecognized role at the Amazon Basin scale. Here we examined the status of several components—hydrology, sediments, freshwater fish biodiversity, and longitudinal river connectivity—that support the ecological integrity of Western Amazon rivers and their linkage to the greater Amazon Basin. Streamflow is largely driven by precipitation and the region supplies nearly all sediments delivered by the Amazon River to the Atlantic Ocean. The Western Amazon harbors 74% of the ichthyofauna of the entire Amazon Basin. Existing dams and road crossings have disrupted longitudinal river connectivity on several rivers. We estimated that 47.8 million people reside in the Amazon Basin, with more than half (58%) inhabiting the Western Amazon. This study helps establish a baseline for tracking change in Western Amazon river ecosystems.